Clinical Effects of Stereotactic Body Radiation Therapy Targeting the Primary Tumor of Liver-Only Oligometastatic Pancreatic Cancer - Ji, Xiaoqin; Zhao, Yulu; He, Chenglong; Han, Siqi; Zhu, Xixu; Shen, Zetian; Chen, Cheng; Chu, Xiaoyuan (Frontiers in Oncology, 2021)
Aim To investigate the efficacy and safety of stereotactic body radiotherapy (SBRT) targeting the primary tumor for liver-only oligometastatic pancreatic cancer. Methods We compared the efficacy and safety of SBRT plus chemotherapy with chemotherapy alone in patients with liver-only oligometastatic pancreatic cancer. The populations were balanced by propensity score-weighted and propensity score-matched analyses based on baseline variables. The primary outcome was overall survival (OS). The secondary outcomes included progression free survival (PFS), local progression, metastatic progression and symptomatic local control. Results This is a retrospective study of 89 pancreatic cancer patients with liver-only oligometastasis. Overall, 34 (38.2%) and 55 (61.8%) patients received SBRT plus chemotherapy and chemotherapy alone, respectively. After propensity score matching, 1-year OS rate was 34.0% (95%CI, 17.8-65.1%) in the SBRT plus chemotherapy group and 16.5% (95%CI, 5.9-46.1%) in chemotherapy alone group (P=0.115). The 6-month PFS rate was 29.4% (95%CI, 15.4-56.1) in SBRT plus chemotherapy and 20.6% (95%CI, 8.8-48.6) in chemotherapy alone group (P=0.468), respectively. Further subgroup analysis indicated that the addition of SBRT improved OS in patients with primary tumor located in the head of pancreas (stratified HR, 0.28; 95% CI, 0.09 to 0.90) or good performance status (stratified HR, 0.24; 95% CI, 0.07 to 0.86). In terms of disease control, SBRT delayed local progression of pancreas (P=0.008), but not distant metastatic progression (P=0.56). Besides, SBRT offered significant abdominal/back pain relief (P=0.016) with acceptable toxicities. Conclusions The addition of SBRT to chemotherapy in patients with liver-only oligometastatic pancreatic cancer improves the OS of those with primary tumor located in the head of pancreas or good performance status. In addition, it is a safe and effective method for local progression control and local symptomatic palliation in patients with metastatic pancreatic cancer.